2017
DOI: 10.1172/jci.insight.91001
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte JAK2 mediates growth hormone–induced hepatic insulin resistance

Abstract: For nearly 100 years, growth hormone (GH) has been known to affect insulin sensitivity and risk of diabetes. However, the tissue governing the effects of GH signaling on insulin and glucose homeostasis remains unknown. Excess GH reduces fat mass and insulin sensitivity. Conversely, GH insensitivity (GHI) is associated with increased adiposity, augmented insulin sensitivity, and protection from diabetes. Here, we induce adipocyte-specific GHI through conditional deletion of (JAK2A), an obligate transducer of GH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 80 publications
2
32
0
Order By: Relevance
“…Circulating FFA originating from adipose tissue as well as directly from nutrition are generally regarded as a major source for ectopic lipid accumulation, and there is evidence that aside from ectopic lipids and adipose tissue, GH-induced lipolysis plays a role in the interorgan transfer of lipids and the induction of IR (32,33). Interestingly, no changes were found in concentrations of FFA species, except (C18:3), which was markedly lower in subjects with ACRO.…”
Section: Table 3 Differences In Metabolomics Between Subjects With Amentioning
confidence: 97%
“…Circulating FFA originating from adipose tissue as well as directly from nutrition are generally regarded as a major source for ectopic lipid accumulation, and there is evidence that aside from ectopic lipids and adipose tissue, GH-induced lipolysis plays a role in the interorgan transfer of lipids and the induction of IR (32,33). Interestingly, no changes were found in concentrations of FFA species, except (C18:3), which was markedly lower in subjects with ACRO.…”
Section: Table 3 Differences In Metabolomics Between Subjects With Amentioning
confidence: 97%
“…Adipose-specific Jak2 KO mice have demonstrated defective lipolysis, increased body weight and adiposity compared to controls, leading to IR (Nordstrom et al, 2013;Shi et al, 2014;Corbit et al, 2017). Similarly, loss of either Stat3 or Stat5 in AT contributes to increased weight gain, adiposity, and impaired lipolysis (Dodington et al, 2018).…”
Section: Molecular Pathways Linking Obesity-induced Inflammation and Irmentioning
confidence: 99%
“…There is a controversy over the effects of adipocyte JAK2/STAT5 on insulin sensitivity. Some studies have shown IR (Shi et al, 2014) while others have demonstrated enhanced whole-body insulin sensitivity in the absence of JAK2 or STAT5 (Nordstrom et al, 2013;Corbit et al, 2017). This inconsistency might be due to a variety of factors including tissue specificity and cell stage-dependent expression of the cre transgene, mouse genetic background, physiologic status, and other environmental factors in which the experiments were performed (Dodington et al, 2018).…”
Section: Molecular Pathways Linking Obesity-induced Inflammation and Irmentioning
confidence: 99%
“…Permanently elevated insulin concentrations in the blood are often considered as an attempt to overcome insulin resistance. Indeed, induction of insulin resistance by genetic disruption of insulin signaling, as well as by increased growth hormone levels or an inflammatory milieu, causes hyperinsulinemia [68][69][70]. The opposite causality is of more relevance.…”
Section: Detrimental Combination Of Hyperinsulinemia With Insulin Resmentioning
confidence: 99%